PENDIDIKAN SEKSUAL ONLINE UNTUK REMAJA: NARASI KONTEN DAN KOMENTAR DI TABU.ID - Alda Retania, Vira; Hasfi, Nurul; Luqman, Yanuar (Interaksi Online, 2024)
This research describes the situation of sexual education in Indonesia, where "sex" is still considered taboo and there are many misconceptions about sexuality. Parents, schools, and mass media still provide inadequate information, leading adolescents to seek information from social media platforms like Instagram. In this context, the Instagram account @tabu.id plays a significant role in providing comprehensive sexual education and reproductive health. This study explores the narratives presented by @tabu.id in its sexual education content and the culture reflected through Instagram users' responses to that content. The research employs an interpretive paradigm with theories of Computer Mediated Communication and New Media. A qualitative approach using the netnography method is utilized to analyze 20 posts from @tabu.id with the highest likes and comments from January 2022 to September 2023. The findings reveal 5 categories in the Sexual Education and Reproductive content uploaded by Tabu.id: Sexual Orientation and Gender, Sexual and Reproductive Health, Relationships, Sexual Activities, and Sexual Violence. Tabu.id has facilitated significant open discussions about sexual education and reproduction on its Instagram account. Through discussions in the comment section, netizens exchange experiences and information, reflecting openness, inclusivity, and courage to discuss issues of sexual education, highlighting the importance of social media in voicing opinions on taboo and sensitive issues like sexual education and reproduction.